SAT0082 Incidence and Survival of Biopsy-Proven GIANT Cell Arteritis in Northern Italy. (10th June 2014) - Macchioni, P.; Catanoso, M.; Boiardi, L.; Muratore, F.; Restuccia, G.; Chiarolanza, I.; Cavazza, A.; Luberto, F.; Salvarani, C.
Abstract : Objectives: To investigate the incidence and mortality of biopsy proven giant cell arteritis (GCA) over a 27-year period in a defined area of northern Italy. Methods: All patients with incident GCA diagnosed from January 1, 1986 to December 31, 2012 living in the Reggio Emilia area were identified through computerized hospital discharge diagnosis and a structured review of all histopahology reports. Patients were followed up from the time of diagnosis until either their death or December 31, 2013. Results: Two hundred and eighty-seven patients (76 men and 211 women) had biopsy proven GCA according to the histopathological examination. Mean±SD age at diagnosis was 74.3±7.4 years. The mean annual incidence rate (IR) of GCA was 23.08/10 6 (95% CI: 20.5-25.9). The mean IR was 33.3/10 6 (95% CI: 29.0-38.1) among women and 12.4/10 6 (95% CI: 9.8-15.5) for men (p not significant). The lowest IR occurred in male patients in the 50-59 years age group (5.13/10 6 ; 95% CI: 1.4-13.1), the highest IR was observed in female patients 70-79 years age group (153.6/10 6 ; 95% CI: 124.7-187.2). IR difference between sex was significant only in the 60-69 age group (IR male/female 14.6/67.1, 95% CI 7.0-26.9 vs 49.8-88.4). The average annual IR increased from 5.63/10 6 during 1986-1988 to 45.23/10 6 during 1998-2000 period and was stable thereafter with IR of 30-23/10 6 .At histological examination 13.6% (39 pts) had only small vessels perivascular involvement (adventitial vasa vasorum and peri-adventitial capillaries). Prevalence of small vessels involvement was significant higher among male patients (male 30% vs 7%female, p<0.001).One hundred and twenty-one patients (42.2%) died during the follow-up period (median survival after diagnosis 152 months [range 4-320 months]). Survival did not differ nor between gender or between different histopathological pattern. Conclusions: This population-based study is the first to report the incidence of biopsy proven GCA in Italy. Our average annual IR is similar to that reported in the period 1984-1988 in Finland (1). Unlike the Spanish data our annual IR is higher among women than among men (2). References: Franzén P, Sutinen S, von Knorring J. Giant cell arteritis and polymyalgia rheumatica in a region of Finland: an epidemiologic, clinical and pathologic study, 1984-1988. J Rheumatol. 1992;19:273-6. Gonzalez-Gay MA, Miranda-Filloy JA, Lopez-Diaz MJ, Perez-Alvarez R, Gonzalez-Juanatey C, Sanchez-Andrade A, Martin J, Llorca J. Giant cell arteritis in northwestern Spain: a 25-year epidemiologic study. Medicine (Baltimore). 2007;86:61-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5523